DESAIN MOTIF BATIK CIMAHI SEBAGAI WUJUD IDENTITAS BUDAYA DALAM KACAMATA ANTROPOLOGI - Diva Rohisa (Brikolase, 2022)
The purpose of this study is to identify how Cimahi batik is a form of cultural identity. So that the younger generation, especially the people of Cimahi City, can know and appreciate the form of cultural heritage in the form of one of the city's identities. The research method used is a qualitative method by analyzing the data found. This study uses a literature/library study approach in which the data comes from various literatures, both in print and electronic media related to cultural identity in the form of urban batik in the view of anthropology. This is motivated by the swift currents of globalization which can cause cultural shifts. Even the cultural identity of an area can be lost if it is not preserved. So this research is expected to increase the sense of respect and pride in the existing cultural identity.